Causes and Risk Factors of Cerebral Ischemic Events in Patients With Atrial Fibrillation Treated With Non–Vitamin K Antagonist Oral Anticoagulants for Stroke Prevention: The RENo Study. Issue 8 (August 2019) - Paciaroni, Maurizio; Agnelli, Giancarlo; Caso, Valeria; Silvestrelli, Giorgio; Seiffge, David Julian; Engelter, Stefan; De Marchis, Gian Marco; Polymeris, Alexandros; Zedde, Maria Luisa; Yaghi, Shadi; Michel, Patrik; Eskandari, Ashraf; et al.
Abstract : Background and Purpose—: Despite treatment with oral anticoagulants, patients with nonvalvular atrial fibrillation (AF) may experience ischemic cerebrovascular events. The aims of this case-control study in patients with AF were to identify the pathogenesis of and the risk factors for cerebrovascular ischemic events occurring during non–vitamin K antagonist oral anticoagulants (NOACs) therapy for stroke prevention. Methods—: Cases were consecutive patients with AF who had acute cerebrovascular ischemic events during NOAC treatment. Controls were consecutive patients with AF who did not have cerebrovascular events during NOACs treatment. Results—: Overall, 713 cases (641 ischemic strokes and 72 transient ischemic attacks; median age, 80.0 years; interquartile range, 12; median National Institutes of Health Stroke Scale on admission, 6.0; interquartile range, 10) and 700 controls (median age, 72.0 years; interquartile range, 8) were included in the study. Recurrent stroke was classified as cardioembolic in 455 cases (63.9%) according to the A-S-C-O-D (A, atherosclerosis; S, small vessel disease; C, cardiac pathology; O, other causes; D, dissection) classification. On multivariable analysis, off-label low dose of NOACs (odds ratio [OR], 3.18; 95% CI, 1.95–5.85), atrial enlargement (OR, 6.64; 95% CI, 4.63–9.52), hyperlipidemia (OR, 2.40; 95% CI, 1.83–3.16), and CHA2 DS2 -VASc score (OR, 1.72 for each point increase; 95% CI, 1.58–1.88) were associated with ischemic events. Among the CHA2 DS2 -VASc components, age was older and presence of diabetes mellitus, congestive heart failure, and history of stroke or transient ischemic attack more common in patients who had acute cerebrovascular ischemic events. Paroxysmal AF was inversely associated with ischemic events (OR, 0.45; 95% CI, 0.33–0.61). Conclusions—: In patients with AF treated with NOACs who had a cerebrovascular event, mostly but not exclusively of cardioembolic pathogenesis, off-label low dose, atrial enlargement, hyperlipidemia, and high CHA2 DS2 -VASc score were associated with increased risk of cerebrovascular events.